Kebijakan Anggaran Dana Keistimewaan Daerah Istimewa Yogyakarta - Sakir Sakir; Dyah Mutiarin (Universitas Muhammadiyah Yogyakarta, 2015)
As a country where the economic system still depend on financing of the public sector, the expectation that decentralizationpolicy in Indonesia can improve significantly society welfare has not been fulfilled yet. Happened in Yogyakartawhich has special authority in control government affairs. Constitution no 13 years 2012 about DIY privileges consistof 5 things like filling the positions, seat, job and authorities governor and vice governor, institutional affairs, cultureaffairs, land affairs, and spatial affairs. With the constitution expected DIY government can guarantee right of societyto live in prosperity. However, the expectation still can not fulfilled either. This study aims to identify and explain thepolicy configuration of DIY Privileged Funds and determine the contribution of the DIY privileged funds in publicwelfare acceleration. The research type used is a qualitative approach. Data collection methods technique is deptinterview and elite interviews, and documentation.